Evaluation of Flexural and Flame Retardant Properties of Recycled Polyethylene Terephthalate – Silica Sand Composites - Johari, Iman Nur Sazniza; Badarulzaman, Nur Azam (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research focuses on the evaluating the mechanical properties of the polymer composites made with recycled polyethylene terephthalate (PET) and silica sand. The mechanical testing focuses in this research are bending test and fire retardant test. The objectives of this research are to produce a composite material from mixture of PET and silica sand and also to evaluate the mechanical properties of PET-silica sand composites. The materials used in this researcher PET and silica sand where PET can be obtained from the recycled plastic bottles. Several parameters were considered such as varying the sand particle weight percentage such as 20 %, 30 %, 40 % and 50 %. The results for bending test and fire retardant test were obtained, however, they do not verify by the previous research. It can be concluded that the mechanical properties of PET-silica sand composite was successfully evaluated.